Acculturation and its discontents : the Italian Jewish experience between exclusion and inclusion - Myers, David N.; Myers, David N.; University of California, Los Angeles. Center for 17th- & 18th- Century Studies; William Andrews Clark Memorial Library (UCLA Clark Memorial Library series, 2008)
Exploring the fascinating cross-cultural influences between Jews and Christians in Italy from the Renaissance to the twentieth century, Acculturation and Its Discontents assembles essays by leading historians, literary scholars, and musicologists to present a well-rounded history of Italian Jewry.The contributors offer rich portraits of the many vibrant forms of cultural and artistic expression that Italian Jews contributed to, but this volume also pays close attention to the ways in which Italian Jews - both freely and under pressure - creatively adapted to the social, cultural, and legal norms of the surrounding society. Tracing both the triumphs and tragedies of Jewish communities within Italy over a broad span of time, Acculturation and Its Discontents challenges conventional assumptions about assimilation and state intervention and, in the process, charts the complex process of cultural exchange that left such a distinctive imprint not only on Italian Jewry, but also on Italian society itself.This collection of rigorous and thought-provoking essays makes a major contribution to both the history of Italian culture and the cultural influence and significance of European Jews.
Keywords: Jews : Italy : History; Jews : Cultural assimilation : Italy; Jews : Italy : Social conditions; Italy : Ethnic relations